2014
DOI: 10.1055/s-0033-1361513
|View full text |Cite
|
Sign up to set email alerts
|

Klinisches Bild und Diagnostik des angeborenen portosystemischen Shunts beim Hund

Abstract: Im Gegensatz zum Menschen, bei dem ein erworbener portosystemischer Shunt meist nur sekund?r durch Erkrankungen der Leber auftritt, kommt der portosystemische Shunt beim Hund ?fter angeboren als erworben vor. Die H?ufigkeit der Erkrankung wird kritisch diskutiert. Man geht jedoch von einer erheblichen Dunkelziffer aus, insbesondere weil die Symptome mannigfaltig sind und die Auspr?gung sehr unterschiedlich ist. Die Erkrankung z?hlt zu den beim Hund be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…The results of this study confirm many previously reported aspects of PSSs in dogs. This includes that many dogs with PSSs in our study were purebred dogs, breeds commonly over-represented in studies on PSSs (e.g., Bolonka Zwetna, Yorkshire Terrier, Malteser, and Labrador Retriever), and of very young age [ 1 , 2 , 4 ]. However, some dogs included in our study had a later presentation, supporting the idea that the onset of clinical signs may occur at any age [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The results of this study confirm many previously reported aspects of PSSs in dogs. This includes that many dogs with PSSs in our study were purebred dogs, breeds commonly over-represented in studies on PSSs (e.g., Bolonka Zwetna, Yorkshire Terrier, Malteser, and Labrador Retriever), and of very young age [ 1 , 2 , 4 ]. However, some dogs included in our study had a later presentation, supporting the idea that the onset of clinical signs may occur at any age [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…This includes that many dogs with PSSs in our study were purebred dogs, breeds commonly over-represented in studies on PSSs (e.g., Bolonka Zwetna, Yorkshire Terrier, Malteser, and Labrador Retriever), and of very young age [ 1 , 2 , 4 ]. However, some dogs included in our study had a later presentation, supporting the idea that the onset of clinical signs may occur at any age [ 1 ]. The majority of the dogs were diagnosed with an extrahepatic PSS, a more common finding in smaller breeds [ 35 ], which comprised the majority of our study population.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations